COMMUNITY PARTICIPATION IN THE PRESERVATION OF THE RELIGIOUS TOURISM SITE OF THE TOMB OF PUTRI PINANG MASAK - Muhtadin, Sabilul; Saputra, Ardi; Helmi, Heny (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to determine community participation in preserving the religious tourism site of the tomb of Putri Pinang Masak in Senuro Village, Tanjung Batu District, Ogan Ilir Regency. The research population was 7 people with a purposive sampling method, namely determining samples based on certain considerations. These considerations, for example, choosing individuals who are considered to have the most relevant knowledge of the information needed or have influence in the environment being studied, so that it can make it easier for researchers to understand the objects or social situations being studied. The results of the study that can involve the community in maintaining and preserving the religious tourism site of the Tomb of Putri Pinang Masak in Senuro Village have a fairly large role, although not yet fully maximized. Community participation is manifested in various forms, both directly through physical activities and indirectly such as providing donations and ideas. Activities such as mutual cooperation, maintenance of the tomb environment, and material and labor support show concern for the preservation of this historic site